Immediate and sustained effects of user fee exemption on healthcare utilization among children under five in Burkina Faso: a controlled interrupted time-series analysis - Zombré, David; De Allegri, Manuela; Ridde, Valéry (Social science & medicine, 2017)
Background: Little is known about the long-term effects of user fee exemption policies on health care use in developing countries. We examined the association between user fee exemption and health care use among children under five in Burkina Faso. We also examined how factors related to characteristics of health facilities and their environment moderate this association. Method: We used a multilevel controlled interrupted time-series design to examine the strength of effect and long term effects of user fee exemption policy on the rate of health service utilization in children under five between January 2004 and December 2014. Results: The initiation of the intervention more than doubled the utilization rate with an immediate 132.596% increase in intervention facilities (IRR: 2.326; 95% CI: 1.980 to 2.672). The effect of the intervention was 32.766% higher in facilities with higher workforce density (IRR: 1.328; 95% CI (1.209-1.446)) and during the rainy season (IRR:1.2001; 95% CI: 1.0953-1.3149), but not significant in facilities with higher dispersed populations (IRR: 1.075; 95% CI: (0.942-1.207)). Although the intervention effect was substantially significant immediately following its inception, the pace of growth, while positive over a first phase, decelerated to stabilize itself three years and 7 months later before starting to decrease slowly towards the end of the study period. Conclusion: This study provides additional evidence to support user fee exemption policies complemented by improvements in health care quality. Future work should include an assessment of the impact of user fee exemption on infant morbidity and mortality and better discuss factors that could explain the slowdown in this upward trend of utilization rates three and a half years after the intervention onset.